BUSINESS DEVELOPMENT STRATEGY ON AVERHOA TEA PRODUCTS IN BLITAR CITY - Rona Asmara; Luhur Aditya P (Universitas Islam Balitar, 2023)
The Karangsari area of Blitar City has many natural resources, especially sweet star fruit, almost all surrounding communities make a living star fruit farmers and also have businesses that diversify sweet star fruit into various preparations such as sweets, syrups, meatballs, and many more. This Averrhoa Tea product is a new product which is one of the results of the diversification of sweet star fruit. The problem faced by the new product is that there is no product development so that people are still hesitant to try Averrhoa Tea products. This study aims to identify the right strategy in product development at Averrhoa Tea business in Blitar City. The location of this research was conducted in Blitar City. This study was conducted for 1 month, from May to June 2023. The data used in this study are primary data and secondary data. Primary data is data obtained directly from the research location through ...